Assessment of College Student’s Awareness in Relation to Solar Energy Products in Coimbatore District - P. , Easwaran; S. , Rani; P. , Nagalakshmi (International Journal of Psychosocial Rehabilitation, 2020)
Solar energy is becoming popular renewable energy around the world, and now it is becoming more popular for generating electricity. Solar products are easily installed and easily maintained. Solar products will help control electricity bills. Still, we are able to see many households have not utilized solar products benefits due to major factors of awareness, cost, etc. This study focuses on awareness among the college students. This study is descriptive in nature. 200 samples are collected from various colleges in Coimbatore district. Through this study, students’ awareness of solar products has been analyzed, and proper suggestions and conclusions are provided.